THE SYNTACTIC PROPERTIES AND DISTRIBUTIONS OF PERSONAL PRONOUNS INSAMBORI LANGUAGE - Arafiq, Arafiq; Hanafi, Nurrachman; Mu'adz, Muhammad Husni; Yusra, Kamaluddin (Universitas Muhammadiyah Surakarta, 2018)
This article aims at describing the syntactic properties and distributions of Personal Pronouns in Sambori Language, a language spoken by the people who occupy Sambori Village and others nearby villages in Lambitu, a montainous district of Bima Regency. Sambori Language is claimed to be a different language from Bima Language due to its characteristic of which sounds are different from those of Bima Language. This fact is used by the people of Sambori to legimate their existence by reffiring the language they speak as Inge Ndai. However, no research documentations have proved that Sambori Language belongs to a single language which is classified into a particular group or sub group under the Austronesian Language group. This study deals with the documentation of the syntactic properties and distributions of Sambori Language which focuses on describing the personal pronoun system of the language, describing types of personal pronouns and their syntactic properties and distributions. The data of this study were taken from elicitation, interview, and decumentation. The result of the study shows that Sambori Language has a set of morphologically independent personal pronouns (full pronouns) and a set of clitics. These two sets of personal pronouns show a different syntactic properties and distributions. Only full pronouns which can occur as independent clausal arguments of both intransitive and transitive constructions. In addtion to their distributions, clitic pronouns cannot occur with numerals, relatives, demonstarives, and NPs as the full pronouns can. This sytactical evidences show that Sambori language is different from Bima Language. Keywords: personal pronoun, clitics, synactic distribution, Sambori Language